Patterns of Simile in The Poetry of Bitushi - Attaa Tahir Abdullah; Hishyar Zaki Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study aims to identify the analogy style and its patterns of Al- Bitoshi by describing the analogy as an essential graphic art that helps to create the poetic image and adds artistic dimensions to it that increase the power of influence on the recipient. Al-Bitoshi is regarded as a well-known scholar in the 18th century in Iraq. He was a versed scholar in Islamic and Arab sciences; his writings are evidence in those sciences, in addition to his literature (from literary letters and poems) that are rich in meanings, powerful in expression, and can transform between graphic arts and creative arts. Among the graphic arts is the analogy frequently used in its systems and multiplicity of styles. His ability to weave visual images full of vitality and movement derived from the Arab environment and fused into his poetic imagination gave significance and aesthetics to his poems. This is the main reason behind choosing Al- Bitoshi’s poems and studying it in this research.